1997
DOI: 10.1007/s004210050314
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and physical fitness of elderly sportsmen

Abstract: The nutritional status of elderly sportsmen has not been reported on, neither has the nutritional balance nor the precise relationship between nutritional status and physical fitness been detailed for this population. Thus, group of 18 sportsmen [age 63 (SD 4.5) years] was monitored by weighing their food during a 6-day period. Macro nutrient, mineral and vitamin content was derived from tables. Daily energy expenditure (DEE) and sport activity (DSA) were quantified over a 7-day period using a questionnaire. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…It was concluded that the energy intake was greater for the master athletes of this study than the energy intake (1632kcal/day) reported by the US Department of Agriculture for non-athletic women of similar age (50-59 years). In another study conducted in Europe, Chatard et al (1998) found similar results in a group of 23 master athletes (mean age: 63 years) practicing mainly aerobic activities (cycling, running, swimming, tennis and walking) for an average of 2.6h per day. The average daily energy intake was higher (+24%) than the RDA at the time.…”
Section: Challenge N°1: Resisting To Reduced Energy Intakesupporting
confidence: 58%
“…It was concluded that the energy intake was greater for the master athletes of this study than the energy intake (1632kcal/day) reported by the US Department of Agriculture for non-athletic women of similar age (50-59 years). In another study conducted in Europe, Chatard et al (1998) found similar results in a group of 23 master athletes (mean age: 63 years) practicing mainly aerobic activities (cycling, running, swimming, tennis and walking) for an average of 2.6h per day. The average daily energy intake was higher (+24%) than the RDA at the time.…”
Section: Challenge N°1: Resisting To Reduced Energy Intakesupporting
confidence: 58%
“…It was concluded that the energy intake was greater for the master athletes of this study than the energy intake (1632 kcal/day) reported by the US Department of Agriculture for non-athletic women of a similar age (50-59 years). In another study conducted in Europe, Chatard et al (1998) found similar results in a group of 23 master athletes (mean age: 63 years) practicing mainly aerobic activities (cycling, running, swimming, tennis and walking) for an average of 2.6 h per day. On average, the daily energy intake was higher (+24%) than the RDA at the time.…”
Section: Dietary Habits and Energy Balance Of Master Athletessupporting
confidence: 57%
“…Although micronutrients probably play important roles in physical work capacity and therefore performance through different biological pathways, the relationship between dietary micronutrients and CRF is not well studied in the population sample of adults, especially in large sample sizes. Chatard et al ( 30 ) examined the association between micronutrient intake (eleven nutrient density variables) and CRF in eighteen sportsmen aged 56–72 years. Diet was assessed with a 6-d diet recall and CRF (O 2max ) was objectively measured using a Monark cycle ergometer.…”
Section: Discussionmentioning
confidence: 99%